2020
DOI: 10.5217/ir.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines in irritable bowel syndrome: a comparison with inflammatory bowel disease

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (https://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. 115symptoms are abdominal pain or abdominal discomfort and an altered defecation pattern. As there are, by definition, no biological parameters for diagnostic discretion in IBS, symptoms constitute a reliable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
0
23
0
2
Order By: Relevance
“…Large scale alteration in the gut microbiota, primed on one or more of its entities, can trigger an altered intestinal immune response in the gut mucosa, with a decrease of commensals endowed with anti-inflammatory properties and an increase of those able to trigger an inflammatory response, overall leading to a severe inflammatory state [ 117 , 118 ]. The analysis of inflamed mucosa of IBDs patients has revealed an increased expression of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, IL-12 and tumor necrosis factor (TNF)-α [ 117 , 145 , 146 , 147 ]. In particular, IL-6, whose levels are correlated with the severity of disease, is highly expressed in both serum and tissue of IBDs patients and plays a central role in several immune responses [ 147 , 148 , 149 ].…”
Section: Inflammatory Bowel Diseases (Ibds) and Colorectal Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…Large scale alteration in the gut microbiota, primed on one or more of its entities, can trigger an altered intestinal immune response in the gut mucosa, with a decrease of commensals endowed with anti-inflammatory properties and an increase of those able to trigger an inflammatory response, overall leading to a severe inflammatory state [ 117 , 118 ]. The analysis of inflamed mucosa of IBDs patients has revealed an increased expression of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, IL-12 and tumor necrosis factor (TNF)-α [ 117 , 145 , 146 , 147 ]. In particular, IL-6, whose levels are correlated with the severity of disease, is highly expressed in both serum and tissue of IBDs patients and plays a central role in several immune responses [ 147 , 148 , 149 ].…”
Section: Inflammatory Bowel Diseases (Ibds) and Colorectal Cancer mentioning
confidence: 99%
“…The analysis of inflamed mucosa of IBDs patients has revealed an increased expression of pro-inflammatory cytokines such as IL-1, IL-6, IL-8, IL-12 and tumor necrosis factor (TNF)-α [ 117 , 145 , 146 , 147 ]. In particular, IL-6, whose levels are correlated with the severity of disease, is highly expressed in both serum and tissue of IBDs patients and plays a central role in several immune responses [ 147 , 148 , 149 ]. Of note, IL-6 can lead to nuclear factor (NF)-kB activation and NF-kB nuclear translocation, inducing the expression of intercellular adhesion molecule 1, an important adhesion molecule in the neutrophil-epithelial interactions in IBDs [ 117 , 150 ].…”
Section: Inflammatory Bowel Diseases (Ibds) and Colorectal Cancer mentioning
confidence: 99%
“…Immune activation associated with the release of cytokines is a hallmark of many pathologies [1][2][3][4][5][6] . In extreme cases, this release becomes highly dysregulated worsening the clinical course of the disease 7 .…”
mentioning
confidence: 99%
“…Among the inflammatory diseases, IBDs, which are chronic disorders characterized by inflammation of the gastrointestinal tract, are being increasingly reported around the world [ 23 ]. An analysis of the inflamed mucosa from patients with UC and CD revealed that the pathogenesis of IBDs is related to the enhanced expression of pro-inflammatory cytokines such as IL-1 β, IL-6, TNF-α and IL-8, which induce other mediators that act on the inflammatory tissue, ultimately enhancing the inflammatory response [ 24 , 25 ]. Currently, anti-TNF therapies such as biosimilar anti-TNF monoclonal antibodies are widely used to treat IBD; however, these treatments are limited by factors such as adverse effects [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in IL-1β, IL-6 and TNF-α signaling was found to be effective at inhibiting macrophages in chronic intestinal inflammation, thereby indicating that IL-1β, IL-6 and TNF-α are potential therapeutic targets in IBD [ 30 , 31 ]. Pro-inflammatory cytokine levels are also enhanced in IBD intestinal cells [ 25 ]. To confirm the anti-inflammatory activity of limonoids, we assessed the LPS-induced production of IL-1β, IL-6 and TNF-α using ELISA kits.…”
Section: Discussionmentioning
confidence: 99%